Spatial Clustering and Hotspot Analysis of Dengue Fever in West Java Province, 2020–2024 - Mardhiyah, Lailatul; Suhartono, Suhartono; Raharjo, Mursid; Wahyuningsih, Nur Endah; Sulistiyani, Sulistiyani (Rifa'Institute, 2026)
Introduction: Dengue fever, a vector-borne disease caused by the dengue virus (DENV) and transmitted by Aedes aegypti and Aedes albopictus mosquitoes, has become a major public health problem in West Java, Indonesia. Objective: This study aimed to map high-risk zones of dengue fever in West Java from 2020 to 2024 using spatial analysis techniques. Method: The study used confirmed dengue case data obtained from the West Java Health Profile and applied ArcMap version 10.5 for spatial mapping and analysis, including Global Moran’s Index, Getis-Ord Gi*, Local Indicators of Spatial Association (LISA), and hotspot analysis. Result and Discussion: The results showed a shift in the spatial distribution pattern of dengue cases from random in 2020 to significantly clustered in subsequent years. LISA analysis consistently identified high-high clusters in Bandung Regency, Bandung City, Bogor Regency, Bogor City, Depok City, and Bekasi City, indicating persistent spatial hotspots. Getis-Ord Gi* analysis further confirmed these hotspots with varying levels of statistical significance throughout the study period. Conclusion: These findings indicate the presence of endemic pockets and underscore the need for targeted public health interventions in high-risk areas. This study highlights the value of spatial analysis in understanding disease patterns and in informing evidence-based dengue control strategies in West Java.